Modelagem para apoio ao planejamento das operações de colheita mecanizada no setor sucroenergético - Schmidt, Rene (2021)
In view of the importance of the sugarcane industry in the national and international context, the advance and consolidation of mechanized harvesting in the sector and the relevance of this operation in the production costs of the crop, the present study aimed to develop a mathematical optimization model to scale the plant fleet and to identify the best strategy for allocating the machines in order to guarantee the regular supply of raw materials with the minimum operating cost. A case study was carried out and dedicated software was developed for the purpose. The structured model adequately represented the mechanized sugarcane harvesting system and can be used in the management of the activity for the assessment of scenarios, targeting budgets and management follow-ups. The results obtained allow benefits to the company, contributing to the construction of economic, socio-environmental, tax and operational advantages.